Effect of a body awareness therapy in young healthy - Fregonesi, Cristina Elena Prado Teles; Pelai, Elisa Bizetti; Palma, Mariana Romanholi; Pinto, Mariana de Carvalho; Salgado, Afonso Shiguemi Inoue; Mantovani, Alessandra Madia (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Body Awareness Therapy (BAT) can be used in various clinical settings, in both the prevention and rehabilitation, particularly by improving body awareness, aspects of pain and health mind, however, their scientific evidence is still scarce. Objective: This study aimed to verify the influence of BAT sessions on body awareness in healthy young adults. Method: This is a clinical trial with a sample of young people between 18 and 25, healthy, of both genders, students of the degree course in physiotherapy FCT/UNESP. Data collection occurred in three phases: before the intervention, after the end of 16 sessions (immediate effect) and two months after the latter - follow up (late effect). In general each of these moments data were collected and applied BAQ questionnaire - Body Consciousness Questionnaire. How intervention, 16 sessions of BAT, once a week, lasting 50 minutes was performed. Results: The sample consisted of 28 individuals with 19.85 ± 1.54 years, five males and 23 females. There was improvement in the perception of body awareness (p<0.0001), both immediately after about two months after the intervention program. Conclusion: We conclude, therefore, that after 16 sessions of BAT, one can observe a significant increase in the perception of body awareness of individuals